1961
DOI: 10.1039/jr9610005153
|View full text |Cite
|
Sign up to set email alerts
|

1019. Synthesis of 3-O-p-coumaroylquinic acid

Abstract: A substance previously isolated from cider apples is shown by synthesis Its biogenetic relationship to chlorogenic to be 3-0-p-coumaroylquinic acid. acid is briefly discussed. CHLOROGENIC ACID was first isolated from coffee beans by Gorter who showed it to be a derivative of quinic acid (Ia). Freundenberg showed that the enzyme tannase hydrolysed chlorogenic acid to equimolar amounts of quinic and caffeic acid, and its structure as the 3-caffeic ester (Ib) of quinic acid was later deduced by Fischer and Dangsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…28 This protection can be removed by treatment with hydrazine hydrate in methanol, preferably before removing the protection on the unesterified hydroxy group(s) in the quinic acid residue to minimise acyl migration and saponification of the ultimate CGA. 2 7 Haslam et al 29 preferred benzoylation with removal by palladium-charcoal hydrogenation for the oxidation-sensitive GQA. The protected aroma tic acids can be converted to acyl chlorides by treatment with sulphonyl chloride.…”
Section: Preparation Of the Protected Acyl Chloridementioning
confidence: 98%
See 2 more Smart Citations
“…28 This protection can be removed by treatment with hydrazine hydrate in methanol, preferably before removing the protection on the unesterified hydroxy group(s) in the quinic acid residue to minimise acyl migration and saponification of the ultimate CGA. 2 7 Haslam et al 29 preferred benzoylation with removal by palladium-charcoal hydrogenation for the oxidation-sensitive GQA. The protected aroma tic acids can be converted to acyl chlorides by treatment with sulphonyl chloride.…”
Section: Preparation Of the Protected Acyl Chloridementioning
confidence: 98%
“…Alberti et al 32 reported that 1,3,4-triCQA could be selectively saponified using barium hydroxide to yield 1,4-diCQA. Another approach would be controlled isomerisation of 1,5-diCQA (see Section 3.4 29 used diphenylmethylquinate in the preparation of 1,3,4,5-tetraGQA.…”
Section: For 1-substituted Diacyl Cgamentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Derivatives of QA, such as chlorogenic acid (CGA) ( Figure 1-1), p-coumaryl quinate, etc., are also common in plants. [13][14][15] …”
Section: Qa Structure and Its Derivativesmentioning
confidence: 99%
“…The solvent was removed under high vacuum to get yellow foam. ]undecan-9-one (14). A mixture of quinic qcid (1) (20g, 104.1 mMol), p-totuenesulfonic acid monohydrate (0.2g), 2,2-dimethoxypropane ( 38g, 364 mMol), and acetone ( 100 mL) was heated to reflux for 2 hr.…”
Section: 345-tetraacetoxy-cyclohexanecarboxylic Acid (12)mentioning
confidence: 99%